How does School Experience Relate to Adolescent Identity Formation Over Time? Cross-Lagged Associations between School Engagement, School Burnout and Identity Processing Styles. - Erentaitė, Rasa; Vosylis, Rimantas; Gabrialavičiūtė, Ingrida; Raižienė, Saulė (Journal of Youth & Adolescence, 2018)
The existing research findings still do not provide a clear understanding of the links between adolescent school experience and their identity formation. To address this gap, we analyzed the dynamic links between adolescent school experiences and identity formation by exploring the cross-lagged associations between school engagement, school burnout and identity processing styles (information-oriented, normative and diffuse-avoidant) over a 2-year period during middle-to-late adolescence. The sample of this school-based study included 916 adolescents (51.4% females) in the 9th to 12th grades from diverse socio-economic and family backgrounds. The results from the cross-lagged analyses with three time points revealed that (a) school engagement positively predicted information-oriented identity processing over a 2-year period; (b) school burnout positively predicted the reliance on normative and diffuse-avoidant identity styles across the three measurements; (c) the effects were stable over the three time points and across different gender, grade, and socio-economic status groups. The unidirectional effects identified in our study support the general prediction that active engagement in learning at school can serve as a resource for adolescent identity formation, while school burnout, in contrast, can hinder the formation of adolescent identity. This points to the importance of taking developmental identity-related needs of adolescents into account when planning the school curriculum.